A Stability Indicating HPLC Method for the Determination of Benzophenone-3 and Avobenzone in Cosmetic Formulations - Ceresole, Rita (2013)
An accurate, simple, and reproducible liquid chromatographic method was developed and validated for the determination of benzophenone-3 and avobenzone in a cosmetic formulation. The analyses were performed at room temperature on a reverse-phase C18 column (Inerstil ODS-3) (250 4.6 mm, 5 lm). The mobile phase, which consisted of methanol:water (95:5) and pH 3.2 adjusted with 85% of phosphoric acid, was pumped at a constant flow rate of 1 mL=min. Detection was performed on a UV detector at 315 nm. The method was validated in terms of linearity, precision, accuracy, and specificity by forced decomposition of benzophenone-3 and avobenzone using acid, base, water, hydrogen peroxide, heat, and light. The response of was linear in the range 0.08 to 0.24 mg=mL and 0.04 to 0.12 mg=mL for benzophenone-3 (r2 ¼ 0.9984), and avobenzone (r2 ¼ 0.9925), respectively. The relative standard deviation values for intra- and inter-day precision studies were 0.81 and 0.91 for benzophenone-3 and 1.57 and 1.13 for avobenzone. Recoveries ranged between 99.58 and 101.39 for benzophenone-3 and 98.63 and 102.05 for avobenzone.